Botswana : 2013 Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper examines fiscal policy implications for labor market and economic diversification in Botswana. The IMF report analyzes that large public employment significantly affect labor market outcomes in middle-income countries, including Botswana. It is noted that reforms aimed at reducing the rents and the size of the public sector is likely to significantly improve market outcomes in Botswana. As part of efforts to find new engines of growth and support sustainable long-term and broad-based growth, Botswana has over the years also vigorously pursued policies to diversify the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet